2009
DOI: 10.1016/j.virol.2009.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Lack of in vivo compartmentalization among HIV-1 infected naïve and memory CD4+ T cell subsets

Abstract: Viral compartmentalization between naïve and memory CD4+ T cell subsets has been described, but only for individuals who were receiving antiretroviral therapy (ART). We present here an extensive analysis of the viral quasispecies residing in the naïve, central and effector memory CD4+ T cell subsets in a number of therapy naïve individuals and representing an array of HIV-1 subtypes. We longitudinally analyzed subset-specific infection and evolution in a subtype B infected individual who switches from CCR5 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…Activated CD4 + T cells are the main targets of productive HIV-1 infection. Data from several groups, however, have suggested that cells lacking activation markers are also capable of being infected, and among activated cells there are differences in susceptibility to infection (39)(40)(41)(42)(43). We and others have previously shown considerably higher levels of CD4 + T-cell activation in CP than ES (36,44,45), and activation does not correlate with susceptibility to infection ex vivo in our system (36).…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Activated CD4 + T cells are the main targets of productive HIV-1 infection. Data from several groups, however, have suggested that cells lacking activation markers are also capable of being infected, and among activated cells there are differences in susceptibility to infection (39)(40)(41)(42)(43). We and others have previously shown considerably higher levels of CD4 + T-cell activation in CP than ES (36,44,45), and activation does not correlate with susceptibility to infection ex vivo in our system (36).…”
Section: Resultsmentioning
confidence: 52%
“…We used the same procedure described above to study CD4 + T cells from uninfected donor cells. Because memory cells have previously been shown to be highly susceptible to infection (39,40,51,52), we chose to examine the cell surface markers CD45RA and CCR7, which distinguish memory phenotypes. CCR6, which is a memory cell marker, and the costimulatory markers CD28 and CD27 were also examined (46,53).…”
Section: Resultsmentioning
confidence: 99%
“…2). Interestingly, several studies have demonstrated that R5-tropic virus can be isolated from CD4 ϩ T N cells from HIV-infected individuals (15,17,69,70). There are two possible explanations that could account for the discrepancies between in vitro studies and the in vivo observations: (i) HIV-1 infection systematically upregulates CCR5 expression on T N cells, thus making them more susceptible to infection (71)(72)(73)(74), and/or (ii) R5-tropic virus may be more efficiently transferred to T N cells by plasmacytoid dendritic cells (75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that quantification of viral DNA alone is not necessarily predictive of the size of the inducible latent reservoir and suggests caution in labeling a cellular reservoir of latent HIV-1 as "major" based solely on the frequency of infection. In addition to the memory CD4 ϩ T cell subsets, HIV-1 DNA is almost always detected in T N cells in both viremic and suppressed individuals, although with a much lower frequency than in the T CM and T TM compartments (6,7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Interestingly, in 2013 Saez-Cirion et al reported that in some HIV-1-infected individuals who received ART within 10 weeks of primary infection, viremia could be controlled for at least 24 months posttreatment interruption (8).…”
Section: A Latent Hiv-1 Reservoir Is Established In Resting Cd4mentioning
confidence: 99%
“…However, CCR5 is generally up-regulated with infection and immune activation and CXCR4 is down-regulated (Ostrowski et al 1998), and CCR5-expressing cells are significantly enriched in lymphoid tissue such as the GALT (Agace et al 2000;Anton et al 2000;Veazey et al 2003;Brenchley et al 2004b). Naïve CD4 þ T cells become more extensively infected either by infection with the X4 virus van Rij et al 2000) or by expansion of infection into these cells by both the X4 and R5 viruses (Heeregrave et al 2009). Although R5-to-X4 evolution is common, it is not essential for progression to disease.…”
Section: Target Cells T-cell Subsetsmentioning
confidence: 99%